Ordinances for Defence, in Duke of Yorke's Book of Laws 450 (1664) - (:unkn) unknown (My University, 1671)
Required "every person that can bear arms from 16 to 60 years of age, be always provided with a convenient proportion of powder and bullet fit for service, and their mutual defence." This meant "at least one pound of powder and two pounds of bullet."
Keywords: MILITIAS; REQUIRED POSSESSION